(untitled) (Dhaka University Journal of Biological Sciences, 2026)
The present study examined the effect of gender role orientation on marital adjustment among married adults in Dhaka city. A total of 240 participants (128 males, 112 females) completed the Bangla version of the Bem Sex-Role Inventory to assess gender role orientation—categorized as masculine, feminine, androgynous, or undifferentiated—and the Bangla version of Revised Dyadic Adjustment Scale to measure marital adjustment. One-way ANOVA was used to analyze the data. Results revealed a significant difference in the level of marital adjustment among the four gender role orientation groups, with androgynous individuals exhibiting the highest levels and undifferentiated individuals the lowest. These findings highlighted the importance of gender role orientations in understanding marital dynamics within the sociocultural context of Bangladesh. Dhaka Univ. J. Biol. Sci. 35(1): 141-150, 2026 (January)